Evidence Review and Practice Recommendation on the Material, Design, and Maintenance of Cloth Masks - Sunjaya, Anthony Paulo (Disaster Med Public Health Prep, 2020)
Despite numerous masking recommendations from public health agencies, including the World Health Organization, editorials, and commentaries providing support for this notion, none had examined different homemade masks or demonstrated that perhaps not all cloth masks are the same. This article aims to provide evidence-based recommendations on cloth-mask materials, its design, and, importantly, its maintenance. Articles were obtained from PubMed and preprint servers up to June 10, 2020. Current evidence suggests that filtration effectiveness can range from 3% to 95%. Multiple layer (hybrid) homemade masks made from a combination of high density 100% cotton and materials with electrostatic charge would be more effective than one made from a single material. Mask fit greatly affects filtration efficiency, and adding an overhead knot or nylon overlay potentially provides the best fit for cloth masks. There is a paucity of evidence for masks maintenance as most studies are in the laboratory setting; however, switching every 4 hours as in medical masks and stored in dedicated containers while awaiting disinfection is recommended. Outside of these recommendations to improve the effectiveness of cloth masks to reduce infection transmission, there is a need for countries to set up independent testing labs for homemade masks made based on locally available materials. This can use existing occupational health laboratories usually used for accrediting masks and respirators.